A high-duty-cycle transmitter unit for steady-state surface NMR instruments - N. B. Gaikwad; L. Liu; M. P. Griffiths; D. Grombacher; J. J. Larsen (Geoscientific Instrumentation, Methods and Data Systems)
Groundwater measurements using surface nuclear magnetic resonance (NMR) have been notoriously challenged by a poor signal-to-noise ratio (SNR), but a new steady-state methodology based on long, high-duty-cycle, phase-locked pulse trains has demonstrated huge SNR increases. The hardware requirements for transmitters for steady-state surface NMR are significantly increased compared to transmitters for standard surface NMR use, due to the need for very high pulse-to-pulse stability over long survey times and the increased thermal load caused by a much higher duty cycle. Furthermore, the increased SNR leads to increased production rates, necessitating lightweight equipment that can easily be carried between many field sites during surveys. Here we demonstrate a novel steady-state surface NMR transmitter with a maximum 93 A peak current. The stability of the transmitter is evaluated on 10 min pulse trains with a duty cycle of 10 %, containing pulses of either 5, 10, 20, or 40 ms duration and low or high current. We observe less than 150 ns pulse-to-pulse timing jitter and amplitude variations below 0.4 % between pulses for all pulse durations and currents. During tests, we observe no temperature effects on the timing and current stability. We have designed a customized heatsink, which reduces the transmitter weight by 30 % and the size by 16 % without compromising safe thermal operating conditions. We evaluate the capacitor bank size and current stability and demonstrate that a 10 mF capacitor bank is an appropriate trade-off with insignificant current-drooping in measurements. The extensive analysis and verification demonstrate that the transmitter generates highly stable pulse trains resulting in high-SNR signals.